2018
DOI: 10.1108/sef-08-2016-0207
|View full text |Cite
|
Sign up to set email alerts
|

A territorial perspective of SME’s default prediction models

Abstract: Purpose The purpose of this paper is to test whether the qualitative variables regarding the territory and the firm–territory relationship can improve the accuracy rates of small business default prediction models. Design/methodology/approach The authors apply a logistic regression to a sample of 141 small Italian enterprises located in the Marche region, and the authors build two different default prediction models: one using only financial ratios and one using jointly financial ratios and variables related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Fang He et al (2018) argued that partnership disputes lead to business failure. So, for SMEs it can be vital to have a network with other firms and interested parties (Gabbianelli, 2018). Moreover, cooperation with vertical partners reduces the effect of business failure in manufacturing sectors (Martinez et al, 2019).…”
Section: Business Relationships (Network)mentioning
confidence: 99%
“…Fang He et al (2018) argued that partnership disputes lead to business failure. So, for SMEs it can be vital to have a network with other firms and interested parties (Gabbianelli, 2018). Moreover, cooperation with vertical partners reduces the effect of business failure in manufacturing sectors (Martinez et al, 2019).…”
Section: Business Relationships (Network)mentioning
confidence: 99%
“…The results demonstrate that neural networks and logistic regression outperform alternative strategies. Similarly, Gabbianelli [ 108 ] examined how certain default prediction models for SMEs are implemented by looking at the variables inherent to the territory and enterprise-territory interaction. Moreover, Tobback et al [ 2 ] demonstrated that linking businesses based on their managers and board members enhances the standard bankruptcy prediction by adding complementary predictive power in SMEs.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Future research might be fruitful and intriguing if it expands into a multi-period framework [ 149 ] . Further, a comprehensive understanding of bankruptcy research may be attained by combining individual subjectivity and broader social structure, making a mixed-method approach preferable to a single-method approach [ 108 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Using the Kohonen map-based trajectories, they find that using company prior payment behaviour-related variables improves prediction accuracy, especially for smaller firms and for a horizon longer than one year. Another study (Gabbianelli 2018 ) suggests that variables related to the characteristics of the territory (degree of attractiveness, articulation of the financial system, orientation to innovation) in which the SMEs operate and the firm–territory relationship (degree of territorial rooting, resources of the territory) exert a significant effect on SME default risk.…”
Section: Results Of the Vos Analysis And The Systematic Literature Rementioning
confidence: 99%